Disentangling Causal Ambiguity: Presenting a Formal Model - Qaiyam, Sameer (Prabandhan: Indian Journal of Management, 2009)
Scholars both within Resource Based View (RBV) and outside it have long maintained that Causal Ambiguity is a construct which cannot be strategized, creating a paradox as RBV logic points towards Causal Ambiguity as one of the few constructs, which if strategized properly can lead to Sustainable Competitive Advantage (SCA). Causal Ambiguity, though emerging as one of the most important constructs, has been surrounded by much ambiguity, leading many scholars to call for detailed research to untangle the boundaries of Causal Ambiguity so that the veil surrounding it can be lifted and it can be manipulated for strategizing. Drawing on the recent advancement in Capability and System-Design literature and largely unexplored Routine literature, this paper proposes five testable propositions, which, if proven, can largely help in de-mystifying Causal Ambiguity for the focal firm and help in strategizing it.